Erratum: Profil Kondisi Fisik Pemain Sepakbola Wanita Candra Kirana - Muhammad Akbar Husein AllSabah; Weda Weda; Irwan Setiawan; Aulia Safrotun Nimah (STKIP Muhammadiyah Kuningan, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v4i2.597 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.